(untitled) (TAMADDUN NURI JURNALI, 2024)
In the analysis of the linguistic landscape of the world, it is important to study the issue of a person’s perception of the external world and its reflection in language. The role of associative thinking in the reflection of the world in language, the associative connection of linguistic units, their integration into certain groups according to this connection, their role in creating a sentence or text shows that the associative approach is of high importance. Associative approach to learning a language, methods of associative analysis do not allow learning language materials separately from its owner. On the basis of associative analysis, the perception of reality, cognitive knowledge, linguistic ability, linguistic memory, and reserve of lexical units of the speakers of a certain language are studied. This article the description of the associative space in the Uzbek language, scientific views on it, the relationship between the central and peripheral units of the space, lexical, semantic and syntactic features of the field, and associative units are studied. Based on experience, the formation of syntactic compounds through associative units is analyzed.